ADR in building contracts: special reference to PWD 203A (Rev 2007), PAM 2006 and CIDB Building Works 2000 - Abdul Ghadas, Zuhairah Ariff; Mohd Zafian, Rozina (Sweet & Maxwell Asia, 2010)
In Malaysia, ADR is seen as an alternative to litigation in resolving contractual disputes as it is perceived to be cost saving, more private and able to avoid ill-will or animosity as it sometimes does, in litigation. In the Malaysian construction industry, the present practice of ADR is focused mainly on arbitration. However, with the revised standard forms for construction contract, proposals for the Mediation Act and the Adjudication and Payment Act, there is a strong indication that ADR will be a common feature in resolving construction disputes in Malaysia. This paper intends to highlight the application of ADR in construction contracts with reference to three main standard forms contract in Malaysia: the PWD 203A(2007), the PAM 2006 and the CIDB Standard Form of Contract for Building Works 2000. The main objective of this paper is to analyze existing provisions in these three standard form contracts and to evaluate their significance in providing alternative disputes resolution to parties of construction contracts.